Finger Forces in Clarinet Playing - Hofmann, Alex; Goebl, Werner (Frontiers in Psychology, 2016)
Clarinettists close and open multiple tone holes to alter the pitch of the tones. Their fingering technique must be fast, precise, and coordinated with the tongue articulation. In this empirical study, finger force profiles and tongue techniques of clarinet students (N = 17) and professional clarinettists (N = 6) were investigated under controlled performance conditions. First, in an expressive-performance task, eight selected excerpts from the first Weber Concerto were performed. These excerpts were chosen to fit in a 2 x 2 x 2 design (register: low--high; tempo: slow--fast, dynamics: soft--loud). There was an additional condition controlled by the experimenter, which determined the expression levels (low--high) of the performers. Second, a technical-exercise task, an isochronous 23-tone melody was designed that required different effectors to produce the sequence (finger-only, tongue-only, combined tongue-finger actions). The melody was performed in three tempo conditions (slow, medium, fast) in a synchronization-continuation paradigm. Participants played on a sensor-equipped Viennese clarinet, which tracked finger forces and reed oscillations simultaneously. From the data, average finger force (Fmean) and peak force (Fmax) were calculated. The overall finger forces were low (Fmean = 1.17 N, Fmax = 3.05 N) compared to those on other musical instruments (e.g. guitar). Participants applied the largest finger forces during the high expression level performance conditions (Fmean = 1.21 N). For the technical exercise task, timing and articulation information were extracted from the reed signal. Here, the timing precision of the fingers deteriorated the timing precision of the tongue for combined tongue-finger actions, especially for faster tempi. Although individual finger force profiles were overlapping, the group of professional players applied less finger force overall (Fmean = 0.54 N). Such sensor instruments provide useful insights into player-instrument interactions and can also be used in the future to give feedback to students in various learning and practising situations.